Pertanggungjawaban Pidana Anak Sebagai Pelaku Penyalahguna Narkotika - Dimas Ade Prayogo; Ahmad Yulianto Ihsan; Muridah Isnawati (Academos, 2023)
Drug abuse by children is currently a concern of many people and continues to be discussed and published. In fact, the problem of drug abusers is of concern to various groups. Almost all of them have reminded and wanted the Indonesian people, especially children, to never try and consume narcotics. The purpose of this study is to determine the criminal responsibility of children as narcotics abusers and the legal consequences that can be imposed on children as narcotics abusers. This study used a normative juridical method using a statutory approach. The results of the study indicated that children as perpetrators of narcotics abusers with methamphetamine type can be subject to criminal penalties according to Article 127 number 1 point (a) of Law no. 35 of 2009 concerning narcotics. The explanation of Article 127 number 1 point (a) of the Narcotics Law is that every narcotics abuser of class I for himself can be subject for a maximum imprisonment of 4 (four) years and the legal consequences that can be imposed on a child as a narcotics abuser is that he gets Â½ (one half) criminal witness of the maximum threat of imprisonment for adults in accordance with Article 81 number (2) of Law no. 11 of 2012 concerning the juvenile criminal justice system. In this case, if the prosecutor sues the child as a class I of narcotics abuser based on Article 127 number 1 point (a) of the Narcotics law, the crime penalty which is originally 4 years becomes 2 years.Keywords: Narcotics abusers, Criminal, ChildrenÂ